KAJIAN POTENSI PENGGUNAAN BY PRODUCT INDUSTRI PERTANIAN DI KABUPATEN JEMBER SEBAGAI BAHAN BAKU PEMBUATAN BIOPELLET UNTUK BAHAN BAKAR ALTERNATIF - Andrew Setiawan Setiawan Rusdianto (Agroindustrial Technology, University of Trunojoyo Madura, 2014)
Biopellet is potential alternative fuel sources to be developed that is made from the agricultural industry by product such as cassava, corn, coconut, and rice. The objectives of this study are determine the type of by-product of agricultural industry in Jember which can be used as raw material for making biopellet; know the most potential by-product of agricultural industry in to be a raw material of biopellet. This study consists of three major stages first is preliminary research, identification of agricultural and industrial by-product grading by-product of agricultural industry. The method used in this research is a laboratory analysis and survey.Potential waste rice and corn cobs have relatively the same yield as the number of higher rice production from corn, while corn has a yield greater waste than rice. Therefore, when viewed from the potential waste out of the production of rice and corn, the rice and maize are the most potential of agricultural commodities from agricultural waste amount that comes out. Rice is a potential commodity to be used as raw material waste due to the availability of the industry biopellet. When viewed as a whole the results of the characterization of the physicochemical properties and heat content, it can be seen that the waste oil and waste corn is a commodity that has the potential to be used as raw material for making biopellet.